The effect of ketogenic diet on serum lipid concentrations in children with medication resistant epilepsy. (October 2021) - Yılmaz, Ünsal; Edizer, Selvinaz; Köse, Melis; Akışin, Zeynep; Güzin, Yiğithan; Pekuz, Serdar; Kırkgöz, Hatice Hilal; Yavuz, Merve; Ünalp, Aycan
Highlights: Olive oil-based ketogenic diet may cause dyslipidemia in children with medication-resistant epilepsy. Ketogenic diet causes significant increases in cholesterol and triglyceride levels over the 24-month treatment period. The initial rapid rise in cholesterol and triglyceride levels is followed by a gradually decreasing trend. Cholesterol and triglyceride levels do not rise in patients with pre-existing dyslipidemia. Ketogenic diet can be safely used even in patients with pre-existing dyslipidemia. Abstract: Background: Ketogenic diet (KD) is a valuable treatment option for patients with medication-resistant epilepsy. It is associated with a number of side effects. However limited data are available for the long-term effects of KD on serum lipid levels. Purpose: The aim of this study was to investigate the long-term effects of KD on serum lipid concentrations in children with medication-resistant epilepsy in daily clinical practice. Method: A total of 73 children (40 girls) aged 3 to 193 months (median, 53 months) with medication-resistant epilepsy who received a KD treatment for at least 12 months between 2014 and 2019 years were enrolled in the study. All children were started on a KD with 3:1 ratio which was then adjusted between 2:1 to 4:1 after the onset of KD as clinically necessary. Serum total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride concentrations and body mass index-standard deviation scores (BMI-SDS) were measured at onset and at 1, 6 and 12 months of treatment, and also in 40 of these patients they were measured at 18 and 24 months of treatment. Results: Dyslipidemia was observed in 71.2, 63, 63, 50, and 52.5% of the patients, at 1, 6, 12, 18, and 24 months, respectively. Median total cholesterol and triglyceride concentrations increased significantly at month-1, and although these high levels persisted for 24 months, the increase did not continue and showed a downward trend. However, this increase did not occur in the subset of patients with pre-existing dyslipidemia. Compared to baseline values, total cholesterol and triglyceride concentrations were higher at all time points, except 24-month cholesterol values. During the 24-month treatment period, BMI-SDS increased and the number of antiepileptic drugs decreased significantly. Conclusion: Total cholesterol and triglyceride concentrations appear to increase during the first month of KD treatment, and although these high values persist for 24 months, the increase does not continue, on the contrary, it approaches the normal values by drawing a downward trend. However, cholesterol and triglyceride concentrations do not increase in the subset of patients with pre-existing dyslipidemia.